Application and development of analytic accelerated test models for the lifetime prediction of a novel contacting method - Friedlein, Matthias; Spahr, Michael; Süß-Wolf, Robert; Franke, Jörg (7. WGP-Jahreskongress, 2017)

Development and application of load profiles for thermal qualification testing of receptacle automotive connectors - Friedlein, Matthias; Gräf, Daniel; Stegner, Jonas; Franke, Jörg (Materials Testing, 2021)
Receptacle contacts often are a weak spot of the reliability in electronic systems. During the application phase of the lifecycle, especially in the automotive wiring harness, connectors experience severe loads such as temperature changes. During qualification testing, accelerated tests simulate these thermal stresses. Yet, only the damage mechanisms relevant for service life must be triggered. However, the increasing complexity of electronic components and wiring harnesses demands a continuous adaptation of test strategies. Therefore, this study develops and applies application-oriented load profiles for thermal qualification testing of connectors. Experiments include load profiles inspired by seasonal changes and daily car usage. The tests are carried out on a relative movement test bench as well as in a thermal cycling testing chamber. Contact resistance progression curves, the surface roughness of the contacts, and the area of the stressed contact zones assist in evaluating the effectiveness of the load profiles. All contacts tested during relative movement experiments show no change in contact resistance. The thermal cycling load profile however results in a significant rise in contact resistance. Additionally, the roughness values show varying damages on the contacts due to the different load profiles.
CRIS-Team WoS Importer:2021-04-30

Failure dependent progression of contact resistance in thermal-shock testing of spring-clip contacts - Friedlein, Matthias; Spahr, Michael; Süß-Wolf, Robert; Franke, Jörg (2017 IEEE Holm Conference 2017, 2017)
Through ever changing terms and regulations on fuel consumption and emissions, weight becomes the number one concern of car manufacturers. Meeting those new regulations and the customer's desire for more options and variations is only possible without adding more weight by changing the wiring harnesses' technology. One solution to face this problem can be found by the application of flexible flat cables (FFCs) instead of common round cable wire systems. For a holistic approach, it is important not only to establish automated ways of cable installation, but also methods of automatically contacting components. Therefore, a new direct contacting method was developed at the Institute for Factory Automation and Production Systems (FAPS). The innovative contacting method enables to contact an automatically mounted one side accessible FFC with kinematic systems of industrial robots in an automated way. However, before new technologies can be applied to serial production, car manufacturers demand standardized climatic tests. In this paper, a correlation was discovered between the progression of contact resistance and failure mechanisms during thermal shock testing. Furthermore, an influence of different peak temperatures and materials was identified and the results were verified via SEM micrographs.
Keywords: thermal-shock testing; automotive wire harness; reliability; contact resistance; degradation mechanisms

Innovative signal and power connection solutions for alternative powertrain concepts - Fröhlig, Simon; Piechulek, Niklas; Friedlein, Matthias; Süß-Wolf, Robert; Schmidt, Lorenz; Kuhn, Marlene; Wang, Li; Hefner, Florian; Heisler, Paul; Fröhlich, Jan; Meiners, Moritz; Franke, Jörg (2020 10th International Electric Drives Production Conference (EDPC), 2020)
Since the automotive wiring harness interconnects all electrical components in a vehicle, it also must adapt to all componential, mechanical, and electrical architecture changes. For this reason, almost all trends that affect the vehicle in general also affect the wiring system. This paper describes the current situation, analyses the most important trends in the automotive industry, and discusses their effects on the wiring system. In particular, the focus is on the current megatrend of electromobility and the associated electrification of the powertrain. In addition to the integration of autonomous driving functions and Car-To-X- Communication, the electrification adds new requirements and tasks for the wire harness. In this context, a holistic approach is taken to combine various fields of research such as automation solutions, computer-aided technologies, functional integration, as well as reliability models to offer a solution for the challenges caused by current automotive trends.<br
Keywords: electromobility; wiring harness; vehicle electrical system; signal and power connection; alternative powertrain

New concept for the Integration of Additive Manufactured Mechanical and Mechatronic Components in Aircraft Interior Systems - Gräf, Daniel; Friedlein, Matthias; Gänßmantel, Christopher; Franke, Jörg; Ischdonat, Nils (2020 Advances in Science and Engineering Technology International Conferences (ASET), 2020)

Occurrence and Influence of Fretting Corrosion on Receptacle Contact Resistance - Friedlein, Matthias; Gräf, Daniel; Jaumann, Andreas; Raiser, Fabian; Franke, Jörg (2018 IEEE Holm Conference on Electrical Contacts, 2018)
Over the years, a complex spectrum of reliability testing was set up for electrical components. Necessary, but time- and cost-intensive qualification tests delay the development of new wiring harness components. Consequently, the acceleration of lifetime tests is of crucial importance for identifying and preventing damage mechanisms even before usage. Increased temperatures and relative movements both influence the tendency for fretting corrosion, which is the most relevant damage mechanism in receptacle contacts. This paper designs and constructs a test-setup that aims at introducing damage mechanisms in contacts. To replicate damage occurring during thermal shock testing, thermal and mechanical influences are separated by inducing relative movement between the electrical contacts. Fretting amplitudes taken from literature as well as simulations serve as a basis for the tested micro-movements. To investigate the occurring damage, laser scanning microscopy, an EDX spectrum and analysis of resistance progressions are carried out. The results show a clear correlation between the damage and the induced relative movements. Therefore, the presented test-setup provides realistic test-conditions for investigating degradation mechanisms of receptacle contacts. Further investigations provide the possibility of accelerating qualification investigations by higher fretting frequencies. <br
Keywords: automotive; contact resistance; degradation mechanisms; fretting corosion; reliability; thermal-shock testing; wire harness